The Struggle Against the Reproduction of Historical Amnesia in Schools. A Pedagogical Model for Teaching a Traumatic Historical Memory in Spain (Clepsidra - Interdisciplinary Journal of Memory Studies, 2021)
This article is based on collaborative efforts among institutions of learning, government-supported initiatives in the province of Cádiz (Spain), and civic organizations in order to enhance and promote extracurricular education focused on teaching the Spanish traumatic past. The determining factor in the movement from family secrets shared behind closed doors to today’s memory activists’ public advocacy for the recovery of historical memory, has been the exhumation of the mass graves supported by family members and social activists alike. In this essay, I present the integration of social activism in the teaching and learning process as a means to overcome curricular clichés about the civil war and the Franco repression in Spain. In this way, students are encouraged to develop critical thinking skills and a greater historical understanding of the nation’s past.
Keywords: School, Historical Memory, Social Movements, Critical Pedagogy